2020
DOI: 10.1093/eurheartj/suaa158
|View full text |Cite
|
Sign up to set email alerts
|

Renal arteries denervation with second generation systems: a remedy for resistant hypertension?

Abstract: Initial studies on renal denervation (RDN) for the treatment of non-controlled arterial hypertension (HTN) through radiofrequency ablation of renal arteries demonstrated that RDN is an effective therapeutic strategy to reduce arterial blood pressure (BP). Nonetheless, the first randomized study, SYMPLICITY-HTN-3, failed to demonstrate a clear benefit for RND over the control group. Technologic evolution, with the introduction of new second generation multi-electrode devices, allowed deep energy delivery along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This meta-analysis provides evidence that catheterbased intravascular RDN using second-generation catheters reduces 24-h ambulatory and office BP. Second-generation catheters utilize the multielectrode system that allows simultaneous multisite ablation [24] and allows deep energy delivery along the full circumference of the vessel [25]. The efficiency and speed may be the major characteristics of second-generation catheters as com- pared with first-generation catheters [26].…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis provides evidence that catheterbased intravascular RDN using second-generation catheters reduces 24-h ambulatory and office BP. Second-generation catheters utilize the multielectrode system that allows simultaneous multisite ablation [24] and allows deep energy delivery along the full circumference of the vessel [25]. The efficiency and speed may be the major characteristics of second-generation catheters as com- pared with first-generation catheters [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using first-generation RDN systems could represent a potential explanation for SIMPLICITY HTN-3 trial neutral results. New-generation RDN systems appear to be consistently efficient and safe for blood pressure reduction [ 11 , 12 ]. A recent meta-analysis of nine randomized sham-controlled trials reported contrasting yet noteworthy results [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Initial randomized studies such as Symplicity HTN-1 and the Symplicity HTN-2 had shown promising results of renal denervation in reducing blood pressure levels; 2 , 3 however, in 2014 the Symplicity HTN-3 study, a randomized study comparing RDNs to the placebo group, had shown insignificant differences between the groups of patients studied. 4 , 5 The reasons for these results were many, among them the sample of patients numerically insufficient from a statistical point of view, the inadequate selection of patients, the inexperience of the operators, and the use of first-generation devices. More recent randomized trials were carried out with second-generation devices: the DENERHTN trial, the Spyral HTN-OFF MED trial, the Spyral HTN-ON MED trial and the RARDIANCE-HTN SOLO trial showing how renal denervation resulted in a significant reduction in arterial blood pressure in the outpatient setting.…”
Section: Introductionmentioning
confidence: 99%